Peningkatkan Kemampuan Membaca Kata Melalui Metode Fernald Bagi Anak Gangguan Spektrum Autisme (GSA) (Single Subject Research Kelas V di SLB Al-Azhar Bukittinggi) - Ramadhan, Gita Sandria; Rahmahtrisilvia, Rahmahtrisilvia; Iswari, Mega; Arnez, Gaby; Handayani, Endang Sri (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine whether the Fernald method can help children with Autism Spectrum Disorder improve their word reading skills. The type of research used is an experiment in the form of Single Subject Research (SSR) with an A-B design. The subject of the study was a fifth-grade student with Autism Spectrum Disorder at SLB Al-Azhar Bukittinggi. The data were collected using a word reading ability test as the main instrument. Data analysis was carried out using a visual analysis technique presented in graphical form.The analysis process was conducted over 12 observation sessions. The findings indicated that the hypothesis was accepted based on the established criteria. The change in level between conditions was flat, meaning there was no immediate improvement between the final baseline results and the initial intervention results. However, the trend change between the baseline and intervention conditions increased (+), showing a rising trend from a stable baseline to an improved intervention phase. The data stability was initially inconsistent during the early intervention sessions but eventually demonstrated more consistent improvement. In conclusion, the results of this study show that the Fernald method has a positive impact on improving the word reading ability of children with Autism Spectrum Disorder